Advances in HIV Treatment Discussed - Hoyle, Brian (MD Conference Express, 2014)
This article discusses advances in the treatment of human immunodeficiency virus (HIV) infection and acquired immunodeficiency syndrome (AIDS). Since the introduction of the reverse transcriptase inhibitor azidothymidine (AZT) in 1987, there has been a steady pipeline of drugs gaining approval for use in the United States and elsewhere, with the latest of those being integrase inhibitor dolutegravir in 2013.